ISI PESAN DAN RESPON PENGGUNA AKUN INSTAGRAM SEBAGAI MEDIA INFORMASI WISATA - Muhammad Irfan; Muhammad Najib Hussain; Ikrima Nufikria (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
ABSTRACTThe purpose of this study is to find out and describe the contents of the message and how the response of users of the Instagram account @jelajahsultra as a tourist information media. The research method used in this study is a qualitative research method with the object of this research is that all forms of communication in Instagram @jelajahsultra are carried out by followers of the Instagram account @jelajahsultra with 11 informants. The technique for determining informants in this research is purposive sampling technique. While the data collection techniques used are observation, interviews, and documentation.The results of this study can be concluded that the contents of the message Instagram account @jelajahsultra as a tourist destination media (in the form of photos, videos, and captions) are informative which provides information to followers of Instagram account @jelajahsultra in the beauty of tourist destinations in Sultra. Is persuasive, with travel messages that are packaged in an interesting manner with the right angle of shooting and lighting, so that it can influence or invite followers of the Instagram account @jelajahsultra to travel in accordance with the contents of the message obtained. The response of Instagram account followers @jelajahsultra, not a few followers gave responses like and comments in the form of words, sentences, and emoticons if they thought the message content was good, nicely and liked. While the response of visits and sharing, users of the Instagram account @jelajahsultra shared travel photos by re-uploading travel photos after Instagram @jelajahsultra users visited the tourist based on the message content of the Istagram account @jelajahsultra.Keywords: Message; content; responses; Instagram account; @jelajahsultra.